THE INFLUENCE OF ECONOMIC FACTORS, LIFESTYLE, AND PSYCHOLOGICAL BEHAVIOR ON DECISION-MAKING IN E-WALLET USAGE (A STUDY ON STUDENTS OF THE FACULTY OF ISLAMIC ECONOMICS AND BUSINESS AT UIN SUMATERA UTARA) - Ardhya Redina; Nurlaila; Muhammad Lathief Ilhamy Nasution (International Journal of Cultural and Social Science, 2025)
In the digital era, the use of financial technology, especially e-wallets, is increasing among students due to its convenience and flexibility. However, limited studies have examined the influence of economic, lifestyle, and psychological factors on e-wallet usage, particularly among Islamic economics students. This study uses a quantitative method with a multiple linear regression approach, based on data from 100 respondents collected via online questionnaires. The results show that economic factors negatively influence e-wallet usage (coefficient = -0.276, sig. < 0.05), suggesting that higher economic status may reduce usage. Lifestyle has a positive influence (coefficient = 0.341, sig. < 0.05), indicating students with modern habits are more likely to use e-wallets. Psychological behavior is the most influential factor (coefficient = 0.768, sig. < 0.05), emphasizing the role of motivation, perception, and trust. The R² value of 0.632 indicates that 63.2% of e-wallet usage decisions are explained by these variables.